Comorbidity, physical and mental health among cancer patients and survivors: An Australian population‐based study. Issue 2 (29th March 2017) - Ng, Huah Shin; Roder, David; Koczwara, Bogda; Vitry, Agnes
Abstract: Aim: To assess the prevalence of comorbidities and measures of physical and mental health among the cancer patients and survivors compared with the general population. Methods: Data collected by the Australian Bureau of Statistics from 2011–2012 National Health Survey were utilized for this cross‐sectional study. Comparisons were made between adults aged 25 years and over with history of cancer ( n = 2170) and those respondents who did not report having had a cancer ( n = 11 592) using logistic regression models. Analyses were repeated according to cancer status (current cancer vs. cancer survivor). Results: People with history of cancer had significantly higher odds of reporting mental and behavioral problems (overall cancer group adjusted odds ratio 1.36, 95 percent confidence interval 1.20–1.54; current cancer 2.53, 1.97–3.27; cancer survivor 1.20, 1.05–1.38), circulatory conditions (overall cancer group 1.25, 1.12–1.39; current cancer 1.38, 1.08–1.76; cancer survivor 1.22, 1.09–1.38), musculoskeletal conditions (overall cancer group 1.37, 1.24–1.52; current cancer 1.66, 1.30–2.12; cancer survivor 1.33, 1.19–1.48) and endocrine system disorders (overall cancer group 1.19, 1.06–1.34; current cancer 1.29, 1.00–1.66; cancer survivor 1.17, 1.04–1.33) compared with the noncancer group. Cancer patients and survivors were more likely to report poor health status, a higher level of distress, and a greater number of chronic conditions compared with the noncancer group. Conclusion: Poor health and comorbidity is more prevalent among cancer patients and survivors than the noncancer population. Our results further support the need to develop models of care that effectively address multiple chronic conditions experienced by the cancer population.